Self-gating catalyst of metal oxide semiconductor heterojunction, preparation method and application

By constructing a metal oxide/metal ruthenium heterogeneous interface in electrocatalysts, the problems of high energy consumption and low efficiency in hydrogen production are solved, and efficient dual-function catalytic activity and durability are achieved, which is close to commercial Pt Performance of /C.

CN119303592APending Publication Date: 2025-01-14HUBEI ENG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411271368.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing electrocatalysts have problems of high energy consumption, low efficiency and insufficient catalytic activity in hydrogen production, especially single-function catalysts cannot promote the hydrogen evolution reaction and hydrazine hydrate oxidation reaction at the same time, and the scarcity and high cost of precious metal catalysts such as platinum are limited. Its wide application.

Method used

Using a self-gated catalyst for heterojunction of metal oxide semiconductors, a metal oxide/metal ruthenium heterointerface is constructed through hydrothermal reaction and electrochemical deposition methods, inducing the semiconductor to transform from p-type to n-type, increasing carrier concentration and Catalytic activity.

Benefits of technology

It realizes efficient dual-function catalytic activity, reduces the working voltage and energy consumption of hydrogen production, improves the durability and utilization of the catalyst, and is close to the performance of commercial Pt/C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303592A_ABST
    Figure CN119303592A_ABST
Patent Text Reader

Abstract

The invention provides a self-gating catalyst of a metal oxide semiconductor heterojunction, a preparation method and application, and belongs to the technical field of catalysts. A self-gating catalytic regulation strategy is adopted, a semiconductor is induced to be converted from a p type to an n type by constructing a metal oxide / metal ruthenium heterogeneous interface, and majority carriers are converted from a hole type to a free electron type; the n-type semiconductor heterojunction catalyst has a smaller space charge interval and higher carrier concentration and conductivity; meanwhile, ruthenium sites can provide more excellent catalytic activity sites, and synchronous enhancement of HER and HzOR catalytic activity is achieved. The self-gating catalyst of the metal oxide / metal ruthenium heterojunction is prepared through hydrothermal reaction, air calcination and electrochemical deposition in sequence; the hydrazine hydrate auxiliary hydrogen production system constructed by taking the NiO / Ru catalyst as the cathode and the anode has ultralow electrolytic voltage, high Faraday efficiency, low power consumption and high durability under the current density of 10 mA cm <-2 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a self-gated catalyst of a metal oxide semiconductor heterojunction, a preparation method and an application thereof. Background Art

[0002] Hydrogen (H2) is considered as one of the promising alternative energy carriers due to its zero carbon emission, environmental protection, renewability and high energy density. Compared with traditional technologies such as coal or petroleum gas processing and methane reforming, electrochemical overall water splitting using clean energy (solar or wind energy) is an environmentally friendly and efficient strategy for sustainable production of high-purity green hydrogen. However, due to the slow anodic oxygen evolution reaction (OER, 4OH - → O2 + 2H2O + 4e - , 1.23 V vs. reversible hydrogen electrode, RHE) process, the overall electrochemical water splitting has low energy conversion efficiency (~60%) and high operating voltage (>1.8 V), which leads to high power consumption (>4.5 kWh m -3 H2) limits its widespread application. At present, the more promising energy-saving method for producing H2 is to combine the hydrogen evolution reaction (HER) with the electro-oxidation reaction of thermodynamically favorable organic compounds (such as urea, glucose, chitin, xylose, alcohols, sulfur, 5-hydroxymethylfurfural, 3,4-diaminofurazole, formic acid, aldehydes, amines, etc.) to replace the slow OER process and reduce energy consumption. Among them, the hydrazine oxidation reaction (HzOR, N2H4 + 4OH - → N2 + 4H2O + 4e - , -0.33 V vs.RHE) has attracted widespread attention due to its low thermodynamic oxidation potential. In addition, the HzOR process only produces nitrogen and water without any greenhouse gas emissions. This co-electrolysis strategy significantly reduces the operating voltage of hydrogen production while avoiding the production of O2 and eliminating the risk of explosion of H2 / O2 mixtures, making an efficient and highly safe membraneless electrochemical overall water splitting electrolysis system possible.

[0003] Platinum (Pt) is widely recognized as the most advanced catalyst for HER due to its fast kinetics and good electrical conductivity, which results in near-zero overpotential and extremely low Tafel slope. However, the large-scale application of Pt catalysts is greatly limited by their scarcity, high cost and instability. In contrast, the strength of the metallic hydrogen bond of Ruthenium (Ru) is similar to that of Pt (65 kcalmol -1 ) but costs only one-fifth of platinum, making it a promising alternative. However, the HER activity of ruthenium is significantly limited by the poor behavior of hydrogen adsorption / desorption and the high energy barrier for water dissociation at the ruthenium sites.

[0004] Recently, the construction of supported noble metal catalysts has been widely recognized as an effective method to improve electrocatalytic performance. Generally, combining different species to form a heterogeneous interface can improve the utilization of noble metals, increase the number of catalytic active sites, induce charge transfer, change the charge density, and regulate the adsorption / desorption behavior of reactants / intermediates on active sites, thereby reducing the reaction barrier and promoting the catalytic reaction. For supported noble metal catalysts, commonly used supports include carbon materials, MXenes, metal oxides, metal hydroxides, metal chalcogenides, metal carbides, and metal nitrides, metal phosphides. The chemical properties of the support can significantly change the dispersibility and structural stability of the catalyst, thereby regulating its activity and durability. By selecting a suitable support, the atomic hybrid orbital and electronic structure at the interface between the noble metal and the support can be effectively adjusted. Among them, metal-based supports, such as metal oxides, are anchored by metal nanoparticles through metal-oxygen bonds, thereby forming a heterogeneous structure with strong electron-metal-support interactions, which enhances the dispersibility and stability of metal particles and improves the activity and selectivity of the catalyst. In addition, metal oxides have rich redox properties and actively participate in catalytic redox reactions. Compared with other types of metal compounds, semiconducting transition metal oxides have significant advantages in terms of compositional and structural diversity, providing diversity in the physical / chemical properties of their electronic and crystal structures. However, the catalytic activity of semiconducting oxides is greatly limited due to their low intrinsic carrier concentration and unsatisfactory catalytic activity. In addition, most of the catalysts studied so far are monofunctional catalysts, which are only active for HER or HzOR. Therefore, finding bifunctional electrocatalysts that can promote both HER and HzOR remains a major challenge. Summary of the invention

[0005] In view of the deficiencies of the above-mentioned prior art, the present invention provides a self-gated catalyst, preparation method and application of a metal oxide semiconductor heterojunction. The present invention adopts a self-gated catalytic regulation strategy to construct a metal oxide / metal ruthenium heterointerface to induce the semiconductor to transform from p-type to n-type, thereby achieving efficient bifunctional catalytic activity.

[0006] To achieve the above purpose, the specific technical solutions of the present invention are as follows:

[0007] In a first aspect, the present invention provides a self-gated catalyst for a metal oxide semiconductor heterojunction, which is prepared by a self-gated catalytic regulation strategy through the following method: a metal source and urea are subjected to a hydrothermal reaction to generate a basic metal carbonate on the surface of a conductive substrate, the basic metal carbonate is converted into a metal oxide by air calcination, and finally ruthenium is loaded on the metal oxide by electrochemical deposition in an acidic electrolyte including RuCl3·xH2O, an acid source, and a metal salt to obtain a metal oxide / metal ruthenium heterojunction bifunctional catalyst; the self-gated catalyst for a metal oxide semiconductor heterojunction is a metal oxide / metal ruthenium heterojunction bifunctional catalyst.

[0008] Preferably, the metal source is at least one of metal nitrates, metal chlorides, metal sulfates and acetylacetonate metal salts.

[0009] Preferably, the conductive substrate is one of carbon cloth, carbon paper and nickel mesh.

[0010] Preferably, the metal oxide / metal ruthenium heterojunction bifunctional catalyst is one of NiO / Ru, Co3O4 / Ru, NiCo2O4 / Ru, CuCo2O4 / Ru, ZnCo2O4 / Ru, and Fe2O3 / Ru heterojunction bifunctional catalysts.

[0011] Preferably, the metal oxide / metal ruthenium heterojunction bifunctional catalyst is a NiO / Ru heterojunction bifunctional catalyst.

[0012] Preferably, the metal salt includes but is not limited to potassium chloride or sodium chloride.

[0013] Preferably, the acid source includes but is not limited to hydrochloric acid or sulfuric acid.

[0014] The present invention adopts a self-gated catalytic regulation strategy to construct a metal oxide / metal ruthenium heterointerface to induce the semiconductor to transform from p-type to n-type, realize the transformation of majority carriers from hole type to free electron type, reduce the space charge interval, and increase the carrier concentration and conductivity; at the same time, the ruthenium site can provide a more excellent catalytic active site to achieve efficient bifunctional catalytic activity.

[0015] In a second aspect, the present invention provides a method for preparing the self-gated catalyst of the metal oxide semiconductor heterojunction, comprising the following steps:

[0016] S1. Dissolving a metal source and urea in a solvent to obtain a mixed solution, adding a conductive substrate to the mixed solution, heating the mixed solution at 80-200°C for reaction for 2-24 hours, taking out the conductive substrate, washing and drying the conductive substrate to obtain a conductive substrate having a basic metal carbonate grown on the surface; the basic metal carbonate is a hard nano-needle structure;

[0017] S2, calcining the conductive substrate prepared in S1 at 300-500°C in air for 0.5-4 h to obtain a conductive substrate loaded with metal oxides;

[0018] S3, prepare an acidic electrolyte containing RuCl3·xH2O, an acid source, and a metal salt, use a platinum sheet and a saturated calomel electrode as a counter electrode and a reference electrode respectively, use the conductive substrate loaded with metal oxide prepared in S2 as a working electrode, perform electrochemical deposition, and obtain a self-gated catalyst of a metal oxide semiconductor heterojunction loaded on the conductive substrate after washing and drying.

[0019] Preferably, in step S1, the solvent is deionized water.

[0020] Preferably, in step S1, in the mixed solution, the concentration of the metal source is 0.007-0.14 mol / L, and the concentration of urea is 0.005-0.5 mol / L.

[0021] Preferably, in step S3, in the electrolyte, the concentration of RuCl3·xH2O is 0.0005-0.015 mol / L, the concentration of the acid source is 0.002-0.08 mol / L, and the concentration of the metal salt is 0.005-1.5 mol / L.

[0022] Preferably, in step S3, the voltage of the electrochemical deposition is -1.3~0.1 V vs. SCE, and the scan rate is 10~150 mV s -1 The number of cycles is 5 to 150.

[0023] Preferably, the drying temperature is 50-80° C., and the drying time is 12-24 h.

[0024] In a third aspect, the present invention provides the use of the self-gated catalyst of the metal oxide semiconductor heterojunction or the self-gated catalyst of the metal oxide semiconductor heterojunction prepared by the preparation method in green hydrogen production, including hydrogen evolution reaction and hydrazine hydrate oxidation reaction.

[0025] The technical principle of the method of the present invention is: the present invention obtains a conductive substrate loaded with basic metal carbonate through a simple synthesis path, that is, through a hydrothermal reaction, and then converts the basic metal carbonate into a metal oxide through air calcination, and finally loads metal ruthenium on the metal oxide to prepare a self-gated catalyst for a metal oxide semiconductor heterojunction. In the hydrothermal reaction, the added urea is thermally decomposed to generate ammonium ions and carbonate ions, wherein the carbonate ions and the metal source generate nano-needle-shaped basic metal carbonates, and the ammonium ions provide an alkaline environment for the former. Compared with metal hydroxides, basic metal carbonates will produce more void structures due to decomposition during the calcination process to form NiO, and their morphology is often a one-dimensional structure, which is convenient for forming a one-dimensional cross-linked network structure with a larger specific surface area. The present invention first calcines the basic metal carbonate and then performs an electrochemical deposition treatment, because the electrolyte for the electrochemical deposition of the present invention is acidic, avoiding the negative impact of acid-base reactions on the structure. The present invention prepares an acidic electrolyte, and the metal salt in the electrolyte increases the conductive ions, and its acidic environment can effectively inhibit Ru 3+ The hydrolysis reaction is beneficial to the effective realization of the deposition process.

[0026] The metal oxide / metal ruthenium heterojunction bifunctional catalyst prepared by the present invention takes the NiO / Ru heterojunction bifunctional catalyst as an example: the NiO in the NiO / Ru heterojunction bifunctional catalyst prepared by the present invention has a mutually cross-linked granular nanowire network structure, and the size of the Ru nanoparticles is 5-6 nm; the work function of NiO is 4.26 eV, and the work function of Ru is 5.29 eV; at the NiO / Ru heterogeneous interface, electrons are transferred from NiO to Ru, so that the binding energy of Ni is increased and the binding energy of Ru is reduced, thereby generating electron-rich Ru catalytic sites; at the same time, through the Mott-Schottky curve test, NiO is a p-type semiconductor, while NiO / Ru is transformed into an n-type semiconductor. The NiO / Ru heterojunction bifunctional catalyst of the present invention has a strong interface electronic interaction. The NiO lattice near the heterojunction interface will be stretched to generate tensile stress, so that the oxide energy band changes, thereby inducing the semiconductor to transform from p-type to n-type; the majority carriers transform from hole type to free electron type, reducing the space charge interval, and improving the carrier concentration and conductivity; at the same time, the ruthenium site can provide a more excellent catalytic active site, and the catalytic activity of the NiO / Ru heterojunction bifunctional catalyst for HER and HzOR is simultaneously enhanced.

[0027] Compared with the prior art, the present invention is beneficial in that:

[0028] (1) According to the interface-induced self-gated catalyst construction strategy, the present invention selects p-type or n-type metal oxide semiconductors with very low catalytic activity as carriers, loads Ru clusters by electrodeposition, and forms an oxide / Ru heterostructure with strong interface electronic interaction; through the interface effect, the semiconductor is induced to transform from p-type dominated by holes to n-type dominated by free electrons, thereby enhancing the semiconductor carrier concentration and conductivity, while providing Ru sites with higher catalytic activity, thereby achieving efficient bifunctional catalytic activity.

[0029] (2) For the HER catalytic reaction, the linear scan results of voltammetry at a scan rate of 5 mV / s in 1 mol / L KOH solution showed that the NiO / Ru heterojunction bifunctional catalyst had a high conductivity at 10 mA cm -2 The overpotential at this current density is only 29.3 mV, which is very close to commercial Pt / C (10.4 mV) and Ru (19.2 mV). For the HzOR catalytic reaction, the NiO / Ru heterojunction bifunctional catalyst has a high overpotential at 10, 100, and 500 mA cm -2 The oxidation potentials are -0.079, -0.048, and 0.049 V vs. RHE at different current densities, respectively.

[0030] (3) The hydrazine hydrate-assisted hydrogen production system based on the NiO / Ru heterojunction bifunctional catalyst of the present invention was -2 It has ultra-low electrolysis voltage (0.021 V), high Faradaic efficiency (>99%), low power consumption (0.52 kWh per m 3 H2) and high durability (181 h), indicating that the material has high catalytic activity and excellent durability when used as a catalyst for HER and HzOR in green hydrogen production.

[0031] (4) The method of the present invention has simple steps, is easy to operate, and is easy to scale up for production. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a phase structure result diagram of the NiO / Ru heterojunction bifunctional catalyst prepared in Example 1; wherein, Figure 1 a is the XRD pattern; Figure 1 b. Figure 1 c is the SEM image;

[0033] Figure 2 This is a phase structure result diagram of the NiO / Ru heterojunction bifunctional catalyst prepared in Example 1; wherein, Figure 2 a is TEM image; Figure 2 b is HRTEM image; Figure 2 c. Figure 2d is the HAADF-STEM image; Figure 2 e is the selected area electron diffraction pattern; Figure 2 f is the EDS spectrum; Figure 2 g~2j is the element mapping graph;

[0034] Figure 3 The XPS graph of the NiO / Ru heterojunction bifunctional catalyst and NiO prepared in Example 1; wherein, Figure 3 a is the XPS total spectrum of NiO / Ru and NiO; Figure 3 b is the XPS spectrum of Ni element of NiO / Ru and NiO; Figure 3 c is the XPS spectra of O element of NiO / Ru and NiO; Figure 3 d. Figure 3 e is the high-resolution XPS spectra of Ru element of NiO / Ru and NiO;

[0035] Figure 4 a is the work function of NiO / Ru and NiO; Figure 4 b is the Tauc plot of NiO / Ru and NiO; Figure 4 c is the Mott-Schottky curve of NiO / Ru, Figure 4 d is the Mott-Schottky curve of NiO;

[0036] Figure 5 The HER catalytic performance results of the NiO / Ru heterojunction bifunctional catalyst prepared in Example 1; wherein, Figure 5 a is the polarization curve; Figure 5 b is the overpotential comparison bar graph; Figure 5 c is the Tafel slope result graph; Figure 5 d is the electrochemical active surface area result diagram; Figure 5 e is the normalized result diagram of electrochemical active surface area; Figure 5 f is the turnover frequency result graph;

[0037] Figure 6 The HER catalytic performance results of the NiO / Ru heterojunction bifunctional catalyst prepared in Example 1; wherein, Figure 6 a is the impedance result diagram; Figure 6 b is the stability test result diagram;

[0038] Figure 7 The catalytic performance results of the NiO / Ru heterojunction bifunctional catalyst prepared in Example 1 for HzOR; wherein, Figure 7 a is the polarization curve of different hydrazine hydrate concentrations; Figure 7 b is the polarization curves of different samples at HzOR; Figure 7 c is the Tafel slope result graph; Figure 7 d is the impedance result diagram; Figure 7e is the stability test result diagram;

[0039] Figure 8 The NiO / Ru heterojunction bifunctional catalyst prepared in Example 1 was tested in hydrazine hydrate-assisted hydrogen production; wherein, Figure 8 a is a schematic diagram of a two-electrode electrolytic cell; Figure 8 b is a physical picture of a double-electrode electrolytic cell;

[0040] Fig. 9 The performance results of the NiO / Ru heterojunction bifunctional catalyst prepared in Example 1 in hydrazine hydrate-assisted hydrogen production are shown in FIG. Fig. 9 a is the polarization curve; Fig. 9 b is a voltage comparison bar graph; Fig. 9 c is the result diagram of Faraday efficiency of hydrogen production; Fig. 9 d is a radar chart; Fig. 9 e is the stability result diagram;

[0041] Fig.10 Mott-Schottky curves, HER and HzOR polarization curves of Co3O4 / Ru and Co3O4; Fig.10 a is the Mott-Schottky curve of Co3O4; Fig.10 b is the Mott-Schottky curve of Co3O4 / Ru; Fig.10 c is the HER polarization curve of Co3O4 / Ru and Co3O4; Fig.10 d is the HzOR polarization curve of Co3O4 / Ru and Co3O4;

[0042] Fig.11 Mott-Schottky curves, HER and HzOR polarization curves of NiCo2O4 / Ru and NiCo2O4; Fig.11 a is the Mott-Schottky curve of NiCo2O4; Fig.11 b is the Mott-Schottky curve of NiCo2O4 / Ru; Fig.11 c is the HER polarization curve of NiCo2O4 / Ru and NiCo2O4; Fig.11 d is the HzOR polarization curve of NiCo2O4 / Ru and NiCo2O4;

[0043] Fig.12 Mott-Schottky curves, HER and HzOR polarization curves of CuCo2O4 / Ru and CuCo2O4; Fig.12 a is the Mott-Schottky curve of CuCo2O4; Fig.12 b is the Mott-Schottky curve of CuCo2O4 / Ru; Fig.12 c is the HER polarization curve of CuCo2O4 / Ru and CuCo2O4; Fig.12d is the HzOR polarization curve of CuCo2O4 / Ru and CuCo2O4;

[0044] Fig.13 Mott-Schottky curves, HER and HzOR polarization curves of ZnCo2O4 / Ru and ZnCo2O4; Fig.13 a is the Mott-Schottky curve of ZnCo2O4; Fig.13 b is the Mott-Schottky curve of ZnCo2O4 / Ru; Fig.13 c is the HER polarization curve of ZnCo2O4 / Ru and ZnCo2O4; Fig.13 d is the HzOR polarization curve of ZnCo2O4 / Ru and ZnCo2O4;

[0045] Fig.14 are the Mott-Schottky curves, HER and HzOR polarization curves of Fe2O3 / Ru and Fe2O3; Fig.14 a is the Mott-Schottky curve of Fe2O3; Fig.14 b is the Mott-Schottky curve of Fe2O3 / Ru; Fig.14 c is the HER polarization curve of Fe2O3 / Ru and Fe2O3; Fig.14 d is the HzOR polarization curve of Fe2O3 / Ru and Fe2O3. DETAILED DESCRIPTION

[0046] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] The invention provides a self-gated catalyst for a metal oxide semiconductor heterojunction. The self-gated catalytic regulation strategy is adopted and the catalyst is prepared by the following method: a metal source and urea are subjected to a hydrothermal reaction to generate a basic metal carbonate on the surface of a conductive substrate, the basic metal carbonate is converted into a metal oxide by air calcination, and finally ruthenium is loaded on the metal oxide by electrochemical deposition in an acidic electrolyte comprising RuCl3·xH2O, an acid source and a metal salt to obtain a metal oxide / metal ruthenium heterojunction bifunctional catalyst. The self-gated catalyst for a metal oxide semiconductor heterojunction is a metal oxide / metal ruthenium heterojunction bifunctional catalyst.

[0048] In some examples, the metal source is at least one of metal nitrate, metal chloride, metal sulfate, and acetylacetonate metal salt. In the following specific embodiments, the metal salt is metal nitrate.

[0049] In some examples, the conductive substrate is one of carbon cloth, carbon paper, and nickel mesh. In the following specific embodiments, the conductive substrate is carbon cloth.

[0050] In some examples, the metal oxide / metal ruthenium heterojunction bifunctional catalyst is one of NiO / Ru, Co3O4 / Ru, NiCo2O4 / Ru, CuCo2O4 / Ru, ZnCo2O4 / Ru, and Fe2O3 / Ru heterojunction bifunctional catalysts.

[0051] In some examples, the metal salt includes, but is not limited to, potassium chloride or sodium chloride.

[0052] In some examples, the acid source includes, but is not limited to, hydrochloric acid or sulfuric acid.

[0053] The method for preparing the self-gated catalyst of the metal oxide semiconductor heterojunction comprises the following steps:

[0054] S1. Dissolving a metal source and urea in a solvent to obtain a mixed solution, adding a conductive substrate to the mixed solution, heating the mixed solution at 80-200°C for 2-24 hours, taking out the conductive substrate, washing and drying the conductive substrate to obtain a conductive substrate having a basic metal carbonate grown on the surface; the basic metal carbonate is a hard nanoneedle structure;

[0055] S2, calcining the conductive substrate prepared in S1 at 300-500°C in air for 0.5-4 h to obtain a conductive substrate loaded with metal oxides;

[0056] S3. Prepare an acidic electrolyte containing RuCl3·xH2O, an acid source, and a metal salt, use a platinum sheet and a saturated calomel electrode as a counter electrode and a reference electrode, respectively, use the conductive substrate loaded with metal oxides prepared in S2 as a working electrode, perform electrochemical deposition, and obtain a self-gated catalyst of a metal oxide semiconductor heterojunction loaded on the conductive substrate after washing and drying.

[0057] In some examples, in step S1, the solvent is deionized water.

[0058] In some examples, in step S1, in the mixed solution, the concentration of the metal source is 0.007-0.14 mol / L, and the concentration of urea is 0.005-0.5 mol / L.

[0059] In some examples, in step S3, in the electrolyte, the concentration of RuCl3·xH2O is 0.0005-0.015 mol / L, the concentration of the acid source is 0.002-0.08 mol / L, and the concentration of the metal salt is 0.005-1.5 mol / L.

[0060] In some examples, in step S3, the voltage of the electrochemical deposition is -1.3 to 0.1 V vs. SCE, and the scan rate is 10 to 150 mV s -1 The number of cycles is 5 to 150.

[0061] In some examples, the drying temperature is 50-80° C., and the drying time is 12-24 h.

[0062] Example 1

[0063] A NiO / Ru heterojunction bifunctional catalyst, the preparation steps are as follows:

[0064] S1. Dissolve 4.0 mmol Ni(NO3)2·9H2O and 10 mmol urea (CH4N2O) in 70 mL deionized water and stir for 20 min to obtain a mixed solution a; then transfer the mixed solution a to a polytetrafluoroethylene reactor lining, add cleaned carbon cloth, heat to 120 °C and react for 12 h, cool naturally to room temperature, then wash the carbon cloth substrate with deionized water and ethanol respectively, place in an oven at 80 °C and dry for 12 h to obtain a carbon cloth substrate with basic nickel carbonate grown on the surface; the basic nickel carbonate is a hard nanoneedle structure;

[0065] S2. The carbon cloth substrate prepared in S1 was placed in a muffle furnace, heated to 400 °C, calcined for 2 h, cooled naturally to room temperature and taken out to obtain a carbon cloth substrate with cross-linked NiO nanoneedles grown on the surface;

[0066] S3. Prepare an acidic electrolyte, in which the concentration of RuCl3·xH2O is 5 mmol / L, the concentration of KCl is 0.1 mol / L, and the concentration of HCl is 0.01 mol / L; then use a platinum sheet and a saturated calomel electrode as the counter electrode and the reference electrode, respectively, and use the NiO nanoneedle carbon cloth substrate obtained in step S2 as the working electrode to deposit Ru metal by cyclic voltammetry, with a potential window of -1.0~-0.01 V vs. SCE and a scan rate of 50 mV s -1 , the number of cycles is 40;

[0067] S4. The carbon cloth substrate was cleaned with deionized water and ethanol respectively, and dried in an oven at 80 °C for 12 h to obtain a NiO / Ru heterojunction bifunctional catalyst supported on the carbon cloth substrate.

[0068] The phase structure of the NiO / Ru heterojunction bifunctional catalyst prepared in this example was determined by X-ray diffraction spectrum and TEM image. Figure 1 a is the XRD pattern of NiO / Ru heterojunction bifunctional catalyst, Figure 1In a, the diffraction peaks at 37.3°, 43.4°, 63.0°, 75.6°, and 79.6° correspond to the (111), (200), (220), (311), and (222) crystal planes of NiO (JCPDS card number 01-075-0197), respectively. Figure 1 b. Figure 1 c is the SEM image of the NiO / Ru heterojunction bifunctional catalyst, which shows that the NiO / Ru heterojunction bifunctional catalyst is uniformly attached to the carbon fiber surface. Figure 2 a is the TEM image of NiO / Ru heterojunction bifunctional catalyst, Figure 2 b is the HRTEM image of the NiO / Ru heterojunction bifunctional catalyst. The 2.04 Å and 2.40 Å spacings shown in the high-resolution TEM correspond to the (101) crystal plane of Ru and the (111) crystal plane of NiO, respectively. Figure 2 c. Figure 2 d is the high-angle dark field scanning transmission electron microscopy (HAADF-STEM) image of the NiO / Ru heterojunction bifunctional catalyst. The HAADF-STEM image shows the (002) crystal plane of Ru, showing an obvious NiO / Ru heterojunction interface, and the Ru particle size is 5~6 nm. Figure 2 e is the selected area electron diffraction pattern of NiO / Ru heterojunction bifunctional catalyst, Figure 2 The diffraction rings shown in e correspond to the crystal planes of NiO. No information about Ru is found in the XRD pattern and selected area electron diffraction. This may be due to the small size of Ru particles, which are difficult to detect. Figure 2 f is the EDS spectrum of the NiO / Ru heterojunction bifunctional catalyst, which shows the characteristic peaks of Ni, O, and Ru. Figure 2 g~2j are the element mapping diagrams of NiO / Ru heterojunction bifunctional catalysts, and the element mapping distribution shows the corresponding element distribution.

[0069] Figure 3 The XPS graph of the NiO / Ru heterojunction bifunctional catalyst and NiO prepared in Example 1; wherein, Figure 3 a is the XPS total spectrum of NiO / Ru and NiO, Figure 3 b is the XPS spectrum of Ni element of NiO / Ru and NiO. Figure 3 c is the XPS spectrum of O element of NiO / Ru and NiO, Figure 3 d. Figure 3 e is the high-resolution XPS spectrum of Ru element in NiO / Ru and NiO; the information of the XPS total spectrum and the corresponding Ni, O, and Ru spectra confirms the strong interaction at the NiO / Ru interface. Figure 4a is the work function of NiO / Ru and NiO. The shift of XPS binding energy and work function further confirms that electrons transfer from NiO to Ru to form electron-rich Ru sites. Figure 4 b is the Tauc diagram of NiO / Ru and NiO. The Tauc curve shows that after constructing NiO / Ru, its band gap becomes smaller, which is beneficial to carrier migration. Figure 4 c is the Mott-Schottky curve of NiO / Ru, Figure 4 d is the Mott-Schottky curve of NiO. The Mott-Schottky curve confirms that NiO and NiO / Ru are p-type and n-type semiconductors, respectively.

[0070] The electrocatalytic performance of the NiO / Ru heterojunction bifunctional catalyst prepared in Example 1 was tested by an electrochemical workstation (CHI760E). In the electrocatalytic test, a self-supporting NiO / Ru catalyst electrode, a carbon rod electrode, and a mercuric oxide electrode were used as working electrode, counter electrode, and reference electrode, respectively, to form a standard three-electrode test system. The NiO / Ru electrode was used as the catalytic cathode (1.0 M KOH) of the HER half reaction and the catalytic anode (1.0 M KOH + 0.5 MN2H4) of the HzOR half reaction to form an electrocatalytic coupling system, which was separated by an exchange membrane.

[0071] Figure 5 The HER catalytic performance results of the NiO / Ru heterojunction bifunctional catalyst prepared in Example 1 in 1M KOH electrolyte; wherein, Figure 5 a is a comparison diagram of polarization curves. Figure 5 As can be seen in a, the NiO / Ru heterojunction bifunctional catalyst exhibits impressive catalytic activity with a current density of 10 mA cm -2 , the overpotential is 29.3 mV, which is very close to commercial Pt / C (10.4 mV) and Ru (19.2 mV). Figure 5 b is the overpotential comparison bar graph, from Figure 5 As can be seen in b, at a larger current density, NiO / Ru requires ultra-low overpotentials of 87.8, 129.3, and 215.4 mV to reach 100, 200, and 500 mA cm, respectively. -2 , which is significantly lower than the overpotentials of Pt / C (161.5, 262.5, and 424.8 mV) and Ru (103.8, 163.2, and 285.3 mV). Figure 5 c is the comparison diagram of Tafel slope, from Figure 5 As can be seen in c, the Tafel slope of NiO / Ru is 46.8 mV dec -1 , which is smaller than NiO (263.9 mV dec -1 )、Ru(65.0 mV dec-1 )、Ni pre(215.1 mV dec -1 ) and commercial Pt / C (48.6 mVdec -1 ).

[0072] After Ru nanoclusters are anchored, the sluggish Volmer kinetic mechanism of NiO and Ni pretreatment is transformed into a more efficient Volmer-Heyrovsky mechanism in NiO / Ru. In electrochemical reactions, the apparent activity of a catalyst is closely related to the electrochemically active surface area (ECSA), because a larger ECSA means more active sites for the reaction. In general, ECSA can be calculated using the electrochemical double layer capacitance (C dl ) can be evaluated by scanning the CV curves at various scan rates in the non-Faraday potential range. Figure 5 d is the comparison of electrochemical active surface area results. Figure 5 As can be seen in d, the C dl The values ​​are 27.0, 26.9, 49.8 and 1.3 mF cm -2 Normalizing polarization curves by ECSA is a widely accepted method for evaluating intrinsic activity. Figure 5 e is the comparison of the normalized results of electrochemical active surface area, such as Figure 5 As shown in Figure e, NiO / Ru still exhibits the smallest overpotential, indicating that it has higher intrinsic catalytic activity than NiO, Ru, and Ni precatalysts. In order to gain a deeper understanding of the intrinsic activity of the samples, the turnover frequency (TOF) was calculated. Figure 5 f is the turnover frequency result comparison. Under the overpotential of 200 mV, compared with NiO (0.13 s -1 )、Ru(5.26 s -1 )、Ni pre(0.45 s -1 ) and Pt / C (2.65 s -1 ), the TOF value of the NiO / Ru heterostructure is significantly higher, which is 8.08 s -1 , indicating that the intrinsic activity of each site is enhanced. Figure 6 a is the impedance result comparison, such as Figure 6 As shown in (a), NiO / Ru exhibits the smallest charge transfer resistance compared to NiO, Ru, Ni pre and Pt / C, indicating that HER has excellent interfacial charge transfer kinetics, which confirms that the incorporation of Ru nanoclusters on NiO can indeed enhance HER kinetics. Figure 6 b is the stability test result. Figure 6 As can be seen in b, at 10 mA cm -2After continuous operation for 261 h at a current density of 2.5 Å, NiO / Ru exhibited excellent long-term stability with negligible attenuation.

[0073] Figure 7 The catalytic performance results of the NiO / Ru heterojunction bifunctional catalyst prepared in Example 1 for HzOR; wherein, Figure 7 a is the polarization curve of NiO / Ru heterojunction bifunctional catalyst in electrolytes with different N2H4 concentrations (0~2.0 M); Figure 7 As can be seen from a, in the absence of N2H4, no anodic current density was observed in the potential window of -0.1 to 0.6 V vs. RHE, while the addition of 0.1 M N2H4 solution significantly increased the anodic current density; at the same time, the response current density increased with the increase of N2H4 solution concentration from 0.1 M to 0.5 M; when the N2H4 concentration increased to 2.0 M, the increase in current density was not significant, therefore, 0.5 M N2H4 was used for cost considerations. Figure 7 b is the polarization curves of different samples. Figure 7 As shown in b, at current densities of 10, 100, 300, and 500 mA cm -2 When , the corresponding oxidation potentials of NiO / Ru are -0.079, -0.048, 0.003 and 0.049 V vs. RHE, respectively; compared with NiO and Ru, the performance of the semiconductor heterointerface with interface effect is significantly improved, and is also better than Pt / C. Figure 7 c is the comparison of Tafel slope results, Figure 7 c shows that the Tafel slope of NiO / Ru (8.7 mV dec -1 ) is significantly smaller than NiO (99.8 mV dec -1 )、Ru(9.6 mV dec -1 )、Ni pre(214.3 mV dec -1 ) and Pt / C (25.3 mVdec -1 ), indicating that the HzOR reaction kinetics in the NiO / Ru heterostructure is faster. Figure 7 d is the impedance result comparison, such as Figure 7 As shown in (d), the NiO / Ru heterointerface exhibits a smaller charge transfer resistance than that of Pt / C. Figure 7 e is the stability test result diagram. Figure 7 e shows that NiO / Ru at 10 mA cm -2 The catalyst ran stably for 107 h at a current density of 1.3 Å, demonstrating the excellent HzOR catalytic stability of NiO / Ru.

[0074] The performance of the NiO / Ru heterojunction bifunctional catalyst electrode prepared in Example 1 as the anode and cathode of a two-electrode electrolysis cell was studied in hydrazine-assisted water electrolysis. Figure 6 The performance results of NiO / Ru heterojunction bifunctional catalyst in hydrazine hydrate assisted hydrogen production are shown in Figure 2. Figure 8 a is a schematic diagram of a two-electrode electrolytic cell. Figure 8 b is a physical picture of a double-electrode electrolytic cell. Figure 8 As shown in a, the cathode electrolyte contains 1.0 M KOH, while the anode electrolyte contains 1.0 M KOH / 0.5 M N2H4; Figure 8 As can be seen in b, strong bubbles quickly overflow from the surfaces of each electrode.

[0075] Fig. 9 The performance results of the NiO / Ru heterojunction bifunctional catalyst prepared in Example 1 in hydrazine hydrate-assisted hydrogen production are shown in FIG. Fig. 9 a is the polarization curve, from Fig. 9 As can be seen in a, the NiO / Ru electrolytic cell achieved a charge transfer rate of 10 mA cm at a voltage of only 0.021 V. -2 The current density of 1.58 V is higher than that of 1.67 V in conventional OER / HER electrolyzers due to the sluggish anode OER kinetics, highlighting the key role of HzOR in reducing the voltage of water electrolysis. Fig. 9 b is a voltage comparison bar graph, such as Fig. 9 As shown in b, at a larger current density, the HzOR / OER electrolyzer requires ultra-low voltages of 0.11, 0.22, 0.32, and 0.43 V to achieve 50, 100, 150, and 200 mA cm, respectively. -2 , which is significantly lower than the voltages of OER / HER electrolyzers (1.70, 1.77, 1.82, and 1.88 V). -2 During the electrolysis process, the Faraday efficiency of the gas product was determined using the water displacement method. Fig. 9 c is the result diagram of Faraday efficiency of hydrogen production; Fig. 9 As shown in c, the amount of H2 collected by the HzOR / HER system is very close to the calculated value, indicating a Faradaic efficiency of over 99%; thus, in this coupled system, the H2 -2 The energy consumption required to produce one cubic meter of H2 with an electric current of 0.52 kWh is lower than that of Pt / C (0.87 kWh per cubic meter of H2) and even lower than the theoretical limit of OER / HER systems (2.94 kWh per cubic meter of hydrogen). Fig. 9d is a radar plot, which provides further evidence that the NiO / Ru semiconductor heterostructure bifunctional catalyst has superior performance compared to the commercial Pt / C catalyst. Fig. 9 e is the stability result diagram. The results show that at 10 mA cm -2 Long-term constant current testing of the HzOR / HER electrolyzer at a current density of 2.5 Å showed strong stability and could operate continuously for 181 h.

[0076] Example 2

[0077] A NiO / Ru heterojunction bifunctional catalyst, the preparation steps are as follows:

[0078] S1. 3.0 mmol Ni(NO3)2·9H2O and 8 mmol urea (CH4N2O) were dissolved in 70 mL deionized water and stirred for 20 min to obtain a mixed solution a; then the mixed solution a was transferred to a polytetrafluoroethylene reactor lining, a clean carbon cloth was added, heated to 120 °C and reacted for 6 h, cooled naturally to room temperature, and then the carbon cloth substrate was cleaned with deionized water and ethanol respectively, and placed in an oven at 80 °C for 12 h to obtain a carbon cloth substrate with basic nickel carbonate grown on the surface; the basic nickel carbonate was a hard nanoneedle structure;

[0079] S2. The carbon cloth substrate prepared in S1 was placed in a muffle furnace, heated to 400 °C, calcined for 3 h, cooled naturally to room temperature and taken out to obtain a carbon cloth substrate with cross-linked NiO nanoneedles grown on the surface;

[0080] S3. Prepare an acidic electrolyte, in which the concentration of RuCl3·xH2O is 3 mmol / L, the concentration of KCl is 0.1 mol / L, and the concentration of HCl is 0.01 mol / L; then use a platinum sheet and a saturated calomel electrode as the counter electrode and the reference electrode, respectively, and use the NiO nanoneedle carbon cloth substrate obtained in step S2 as the working electrode to deposit Ru metal by cyclic voltammetry, with a potential window of -1.0~-0.01 V vs. SCE and a scan rate of 50 mV s -1 , the number of cycles is 40;

[0081] S4. The carbon cloth substrate was cleaned with deionized water and ethanol respectively, and dried in an oven at 80 °C for 12 h to obtain a NiO / Ru heterojunction bifunctional catalyst supported on the carbon cloth substrate.

[0082] The NiO / Ru heterojunction catalyst prepared in this example was used as the working electrode. For the HER catalytic reaction, the linear scan results of voltammetry at a scan rate of 5 mV / s in a 1 mol / L KOH solution showed that the NiO / Ru catalyst had a high conductivity at 10 mA cm -2 The overpotential at this current density is only 136 mV. For the HzOR catalytic reaction, the NiO / Ru catalyst has a high current density at 50 and 100 mA cm -2 The oxidation potentials are 0.02 and 0.15 V vs. RHE at the current density, respectively.

[0083] Example 3

[0084] A NiO / Ru heterojunction bifunctional catalyst, the preparation steps are as follows:

[0085] S1. Dissolve 2.0 mmol Ni(NO3)2·9H2O and 7 mmol urea (CH4N2O) in 70 mL deionized water and stir for 20 min to obtain a mixed solution a; then transfer the mixed solution a to a polytetrafluoroethylene reactor lining, add cleaned carbon cloth, heat to 180 °C and react for 6 h, cool naturally to room temperature, then wash the carbon cloth substrate with deionized water and ethanol respectively, place in an oven at 80 °C and dry for 12 h to obtain a carbon cloth substrate with basic nickel carbonate grown on the surface; the basic nickel carbonate is a hard nanoneedle structure;

[0086] S2. The carbon cloth substrate prepared in S1 was placed in a muffle furnace, heated to 400 °C, calcined for 1 h, cooled naturally to room temperature and taken out to obtain a carbon cloth substrate with cross-linked NiO nanoneedles grown on the surface;

[0087] S3. Prepare an acidic electrolyte, in which the concentration of RuCl3·xH2O is 7 mmol / L, the concentration of KCl is 0.15 mol / L, and the concentration of HCl is 0.015 mol / L; then use a platinum sheet and a saturated calomel electrode as the counter electrode and the reference electrode, respectively, and use the NiO nanoneedle carbon cloth substrate obtained in step S2 as the working electrode to deposit Ru metal by cyclic voltammetry, with a potential window of -1.0~-0.01 V vs. SCE and a scan rate of 50 mV s -1 , the number of cycles is 20;

[0088] S4. The carbon cloth substrate was cleaned with deionized water and ethanol respectively, and dried in an oven at 80 °C for 12 h to obtain a NiO / Ru heterojunction bifunctional catalyst supported on the carbon cloth substrate.

[0089] The NiO / Ru heterojunction catalyst prepared in this example was used as the working electrode. For the HER catalytic reaction, the linear scan results of voltammetry at a scan rate of 5 mV / s in a 1 mol / L KOH solution showed that the NiO / Ru catalyst had a high conductivity at 10 mA cm -2 The overpotential at this current density is only 172 mV. For the HzOR catalytic reaction, the NiO / Ru catalyst has a high overpotential at 50 and 100 mA cm -2 The oxidation potentials are 0.06 and 0.23 V vs. RHE at the current density, respectively.

[0090] Example 4

[0091] A NiO / Ru heterojunction bifunctional catalyst, the preparation steps are as follows:

[0092] S1. Dissolve 4.0 mmol Ni(NO3)2·9H2O and 8 mmol urea (CH4N2O) in 70 mL deionized water and stir for 15 min to obtain a mixed solution a; then transfer the mixed solution a to a polytetrafluoroethylene reactor lining, add cleaned carbon cloth, heat to 160 °C and react for 12 h, cool naturally to room temperature, then wash the carbon cloth substrate with deionized water and ethanol respectively, place in an oven at 80 °C and dry for 12 h to obtain a carbon cloth substrate with basic nickel carbonate grown on the surface; the basic nickel carbonate is a hard nanoneedle structure;

[0093] S2. The carbon cloth substrate prepared in S1 was placed in a muffle furnace, heated to 450 °C, calcined for 1 h, cooled naturally to room temperature, and taken out to obtain a carbon cloth substrate with cross-linked NiO nanoneedles grown on the surface;

[0094] S3. Prepare an acidic electrolyte, in which the concentration of RuCl3·xH2O is 3 mmol / L, the concentration of KCl is 0.10 mol / L, and the concentration of HCl is 0.015 mol / L; then use a platinum sheet and a saturated calomel electrode as the counter electrode and the reference electrode, respectively, and use the NiO nanoneedle carbon cloth substrate obtained in step S2 as the working electrode to deposit Ru metal by cyclic voltammetry, with a potential window of -1.0~-0.01 V vs. SCE and a scan rate of 100 mV s -1 , the number of cycles is 60;

[0095] S4. The carbon cloth substrate was cleaned with deionized water and ethanol respectively, and dried in an oven at 80 °C for 12 h to obtain a NiO / Ru bifunctional catalyst supported on the carbon cloth substrate.

[0096] The NiO / Ru heterojunction catalyst prepared in this example was used as the working electrode. For the HER catalytic reaction, the linear scan results of voltammetry at a scan rate of 5 mV / s in a 1 mol / L KOH solution showed that the NiO / Ru catalyst had a high conductivity at 10 mA cm -2 The overpotential at this current density is only 65 mV. For the HzOR catalytic reaction, the NiO / Ru catalyst has a high current density at 50 and 100 mA cm -2 The oxidation potentials are -0.02 and 0.06 V vs. RHE at the current density, respectively.

[0097] Example 5

[0098] A NiO / Ru heterojunction bifunctional catalyst, the preparation steps are as follows:

[0099] S1. Dissolve 5.0 mmol Ni(NO3)2·9H2O and 10 mmol urea (CH4N2O) in 70 mL deionized water and stir for 15 min to obtain a mixed solution a; then transfer the mixed solution a to a polytetrafluoroethylene reactor lining, add cleaned carbon cloth, heat to 160 °C and react for 18 h, cool naturally to room temperature, then wash the carbon cloth substrate with deionized water and ethanol respectively, place in an oven at 80 °C and dry for 12 h to obtain a carbon cloth substrate with basic nickel carbonate grown on the surface; the basic nickel carbonate is a hard nanoneedle structure;

[0100] S2. The carbon cloth substrate prepared in S1 was placed in a muffle furnace, heated to 400 °C, calcined for 2 h, cooled naturally to room temperature and taken out to obtain a carbon cloth substrate with cross-linked NiO nanoneedles grown on the surface;

[0101] S3. Prepare an acidic electrolyte, in which the concentration of RuCl3·xH2O is 5 mmol / L, the concentration of KCl is 0.10 mol / L, and the concentration of HCl is 0.01 mol / L; then use a platinum sheet and a saturated calomel electrode as the counter electrode and the reference electrode, respectively, and use the NiO nanoneedle carbon cloth substrate obtained in step S2 as the working electrode to deposit Ru metal by cyclic voltammetry, with a potential window of -1.0~-0.01 V vs. SCE and a scan rate of 50 mV s -1 , the number of cycles is 80;

[0102] S4. The carbon cloth substrate was cleaned with deionized water and ethanol respectively, and dried in an oven at 80 °C for 12 h to obtain a NiO / Ru bifunctional catalyst supported on the carbon cloth substrate.

[0103] The NiO / Ru heterojunction catalyst prepared in this example was used as the working electrode. For the HER catalytic reaction, the linear scan results of voltammetry at a scan rate of 5 mV / s in a 1 mol / L KOH solution showed that the NiO / Ru catalyst had a high conductivity at 10 mA cm -2 The overpotential at this current density is only 112 mV. For the HzOR catalytic reaction, the NiO / Ru catalyst has a high current density at 50 and 100 mA cm -2 The oxidation potentials were 0.01 and 0.20 V vs. RHE at the current densities, respectively.

[0104] In order to verify the universality of the construction strategy of the present invention, the inventors used hydrothermal synthesis, high-temperature calcination and electrodeposition processes similar to those in Examples 1 to 5, selected some common p-type (Co3O4, NiCo2O4, CuCo2O4, ZnCo2O4) and n-type (Fe2O3) semiconductors, and prepared the corresponding semiconductor heterojunction catalysts (Co3O4 / Ru, NiCo2O4 / Ru, CuCo2O4 / Ru, ZnCo2O4 / Ru and Fe2O3 / Ru). Figures 10 to 14 are the Mott-Schottky curves, HER and HzOR polarization curves of the synthesized semiconductor and its heterojunction catalyst, Figures 10 to 14 It can be seen that after the metal oxide is loaded with Ru clusters, it can be transformed from p-type to n-type; for bimetallic systems including NiCo2O4 / Ru, CuCo2O4 / Ru and ZnCo2O4 / Ru, the Mott-Schottky curve is inverted V-shaped, which may be caused by the uneven loading of Ru clusters on the carrier; at the same time, compared with pure oxides, the carrier concentration of the semiconductor heterojunction loaded with Ru clusters is further increased. In addition, the HER and HzOR catalytic activities of the semiconductor heterojunction were evaluated, and the performance of the semiconductor heterojunction loaded with Ru clusters was significantly improved compared with pure oxides. Therefore, the introduction of Ru clusters on semiconductor metal oxides can construct bifunctional catalysts with high catalytic activity, and this strategy has a certain degree of scalability.

[0105] In summary, the present invention adopts a self-gated catalytic regulation strategy to construct a metal oxide / metal ruthenium heterojunction, induces the semiconductor to transform from p-type to n-type, and realizes the transformation of majority carriers from hole type to free electron type; the n-type semiconductor heterojunction catalyst has a smaller space charge interval, higher carrier concentration and conductivity. At the same time, the ruthenium site can provide a more excellent catalytic active site to achieve the simultaneous enhancement of the catalytic activity of the hydrogen evolution reaction and the hydrazine hydrate oxidation reaction. The present invention uses metal source and urea as raw materials, and sequentially prepares a self-gated catalyst of a metal oxide / metal ruthenium heterojunction through hydrothermal reaction, air calcination, and electrochemical deposition; wherein the hydrazine hydrate-assisted hydrogen production system constructed with NiO / Ru catalyst as cathode and anode is 10 mA cm-2 It has ultra-low electrolysis voltage, high Faradaic efficiency, low power consumption and high durability at low current density.

[0106] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.

Claims

1. A self-gated catalyst for a metal oxide semiconductor heterojunction, characterized in that: The invention adopts a self-gated catalytic regulation strategy and is prepared by the following method: a metal source and urea are subjected to a hydrothermal reaction to generate a basic metal carbonate on the surface of a conductive substrate, the basic metal carbonate is converted into a metal oxide by air calcination, and finally ruthenium is loaded on the metal oxide by electrochemical deposition in an acidic electrolyte including RuCl3·xH2O, an acid source and a metal salt to obtain a self-gated catalyst of a metal oxide semiconductor heterojunction; the self-gated catalyst of the metal oxide semiconductor heterojunction is a metal oxide / metal ruthenium heterojunction bifunctional catalyst.

2. The self-gated catalyst of a metal oxide semiconductor heterojunction according to claim 1, characterized in that: The metal source is at least one of metal nitrate, metal chloride, metal sulfate and acetylacetonate metal salt.

3. The self-gated catalyst of a metal oxide semiconductor heterojunction according to claim 1, characterized in that: The conductive substrate is one of carbon cloth, carbon paper and nickel mesh.

4. The self-gated catalyst of a metal oxide semiconductor heterojunction according to claim 1, characterized in that: The metal oxide / metal ruthenium heterojunction bifunctional catalyst is one of NiO / Ru, Co3O4 / Ru, NiCo2O4 / Ru, CuCo2O4 / Ru, ZnCo2O4 / Ru, and Fe2O3 / Ru heterojunction bifunctional catalysts.

5. The self-gated catalyst of a metal oxide semiconductor heterojunction according to claim 4, characterized in that: The metal oxide / metal ruthenium heterojunction bifunctional catalyst is a NiO / Ru heterojunction bifunctional catalyst.

6. The self-gated catalyst of a metal oxide semiconductor heterojunction according to claim 1, characterized in that: The metal salt includes, but is not limited to, potassium chloride or sodium chloride.

7. The self-gated catalyst of a metal oxide semiconductor heterojunction according to claim 1, characterized in that: The acid source includes, but is not limited to, hydrochloric acid or sulfuric acid.

8. A method for preparing a self-gated catalyst for a metal oxide semiconductor heterojunction, characterized in that: The following steps are involved: S1. Dissolving a metal source and urea in a solvent to obtain a mixed solution, adding a conductive substrate to the mixed solution, heating the mixed solution at 80-200° C. to react, taking out the conductive substrate, washing and drying the conductive substrate to obtain a conductive substrate having a basic metal carbonate grown on the surface; S2, calcining the conductive substrate prepared in S1 at 300-500° C. to obtain a conductive substrate loaded with metal oxides; S3, using the metal oxide-loaded conductive substrate prepared in S2 as a working electrode, electrochemical deposition is performed in an acidic electrolyte comprising RuCl3·xH2O, an acid source, and a metal salt, and after washing and drying, a self-gated catalyst of a metal oxide semiconductor heterojunction loaded on the conductive substrate is obtained.

9. The method for preparing a self-gated catalyst for a metal oxide semiconductor heterojunction according to claim 8, characterized in that: In step S3, in the electrolyte, the concentration of RuCl3·xH2O is 0.0005-0.015 mol / L, the concentration of the acid source is 0.002-0.08 mol / L, and the concentration of the metal salt is 0.005-1.5 mol / L.

10. Use of the self-gating catalyst of the metal oxide semiconductor heterojunction according to any one of claims 1 to 7 or the self-gating catalyst of the metal oxide semiconductor heterojunction prepared by the preparation method according to any one of claims 8 to 9 in green hydrogen production.